High-level secretion of tissue factor-rich extracellular vesicles from ovarian cancer cells mediated by filamin-A and protease-activated receptors - Koizume, Shiro; Ito, Shin; Yoshioka, Yusuke; Kanayama, Tomohiko; Nakamura, Yoshiyasu; Yoshihara, Mitsuyo; Yamada, Roppei; Ochiya, Takahiro; Ruf, Wolfram; Miyagi, Etsuko; Hirahara, Fumiki; Miyagi, Yohei (Thrombosis and Haemostasis, 2016)
Thromboembolic events occur frequently in ovarian cancer patients. Tissue factor (TF) is often overexpressed in tumours, including ovarian clear-cell carcinoma (CCC), a subtype with a generally poor prognosis. TF-coagulation factor VII (fVII) complexes on the cell surface activate downstream coagulation mechanisms. Moreover, cancer cells secrete extracellular vesicles (EVs), which act as vehicles for TF. We therefore examined the characteristics of EVs produced by ovarian cancer cells of various histological subtypes. CCC cells secreted high levels of TF within EVs, while the high-TF expressing breast cancer cell line MDA-MB-231 shed fewer TF-positive EVs. We also found that CCC tumours with hypoxic tissue areas synthesised TF and fVII in vivo, rendering the blood of xenograft mice bearing these tumours hypercoagulable compared with mice bearing MDA-MB-231 tumours. Incorporation of TF into EVs and secretion of EVs from CCC cells exposed to hypoxia were both dependent on the actin-binding protein, filamin-A (filA). Furthermore, production of these EVs was dependent on different protease-activated receptors (PARs) on the cell surface. These results show that CCC cells could produce large numbers of TF-positive EVs dependent upon filA and PARs. This phenomenon may be the mechanism underlying the increased incidence of venous thromboembolism in ovarian cancer patients.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Thrombosis; ovarian cancer; tissue factor; microvesicles; coagulation factor VII